PERTUMBUHAN PADI GOGO DI MEDIUM ULTISOL DENGAN PEMBERIAN CAMPURAN FOSFAT ALAM DAN COCOPEAT PADA DUA KONDISI KADAR AIR - Pedri Antoro; Nelvia Nelvia (Jurnal Solum, 2018)
The main problem of upland rice cultivation in Ultisol are fixation of P, solubility and saturation of Al are the height and water content is low. The research aim to study the effect of interaction of application of mixture of cocopeat with rock phosphate (RP) on growth of upland rice in Ultisols medium at two water content condition. The research  was conducted at the Green House of the Faculty of Agriculture, University of Riau, Pekanbaru from February to July 2017. This research in form factorial experiment was arranged in a completely randomized design. The first factor was mixture of RP with cocopeat consist of 7 levels (0, 30, 45 and 60 kg P2O5/ha each dose + cocopeat dose 10 tons/ha and 30, 45 and 60 kg P2O5/ha without cocopeat). The second factor was water content consists of 2 levels (field capacity and 25% under field capacity), each combination repeated 3 times. The results show the application of rock phosphate dose of 30 kg P2O5/ha + 10 tons cocopeat/ha or without cocopeat increased the growth of upland rice include plant high, number of maximum tiller and productive tiller and dry weight of straw compared to without RP both on the field capacity and 25% below field capacity condition, the increasing of RP dose to 45-60 kg P2O5/ha tended to increase each parameter.Key words : rock phosphate, water content, cocopeat, upland rice.